Inhibitory activity of Carica pubescens leaf extract on cyclooxygenase: anti-inflammatory prospects of natural substances - Sapto Yuliani; Anggoro Wicaksono; Citra Ariani Edityaningrum; Nuri Ari Efiana; Any Guntarti; Sugiyanto; Mustofa Ahda (Pharmaciana, 2026)
Inflammation represents a multifaceted biological reaction that plays a significant role in a variety of chronic pathological conditions and the search for natural anti-inflammatory agents remains a significant focus of pharmacological research. The objective of this study was to assess the in vitro anti-inflammatory properties of an ethanolic extract from the leaf of Carica pubescens (C. pubescens) by examining its effects on cyclooxygenase (COX) enzyme inhibition and conducting protein denaturation assays. An ethanolic extract of the leaf was prepared through maceration using 96% ethanol. Phytochemical screening conducted qualitatively demonstrated that the extract contained flavonoids, alkaloids, saponins, and tannins. Thin Layer Chromatography (TLC) analysis was performed to further identify flavonoids, with quercetin used as the reference standard. The anti-inflammatory activity was assessed using an enzyme immunoassay (EIA) for assessing inhibitory effects on COX-1 and COX-2 and a bovine serum albumin (BSA) denaturation assay. The chromatographic profile of the 96% ethanolic Carica pubescens leaf extract (CPLE 96%) showed a distinct spot with an Rf value comparable to that of quercetin under visible and ultraviolet observation, indicating the presence of quercetin-like flavonoid constituents. The CPLE 96% demonstrated potent, dose-dependent inhibition in both assays. In the protein denaturation assay, the CPLE 96% (100 µg/mL) showed 78.5 ± 2.9 % inhibition, significantly higher than ibuprofen (71.8 ± 2.0 %) and slightly lower than meloxicam (88.4 ± 0.9 %). In the COX inhibition assay, the CPLE 96% exhibited non-selective inhibition with half-maximal inhibitory concentration (IC50) values of 50.42 ± 0.54 µg/mL for COX-1 and 51.18 ± 0.61 µg/mL for COX-2 (Selectivity Index = 0.985 ± 0.017). The findings provide substantial scientific validation for the ethnomedicinal use of C. pubescens, highlighting its dual-acting anti-inflammatory mechanism by inhibiting key inflammatory enzymes and preventing protein denaturation. The extract shows significant potential as a source for developing natural anti-inflammatory therapeutics, warranting further investigation to isolate the active constituents and conduct in vivo studies.